(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The present study collected the opinion of nephrologists from the health centers of the Lambayeque Healthcare Network regarding the referrals sent to the hemodialysis services of the Almanzor Aguinaga Asenjo National Hospital to have sufficient elements and develop a management strategy and the timely referral of predialysis patients. It presents an analytical descriptive design and seeks to characterize the problematic situation experienced by the care centers of the healthcare network. The population consisted of 20 specialist doctors who answered a questionnaire with multiple-choice questions, open questions, and other dichotomous ones, obtaining that 70% of the doctors who refer patients lack adequate training regarding the Management of the technical rules; 50% of the doctors of the reference centers express their dissatisfaction with the system; however, the quality is affected because a significant percentage of general practitioners affirm that they do make a referral correctly, which is why there is considerable inconsistency in the perception of the service; Regarding the continuity for the follow-up of patients on predialysis, 45% of specialist doctors affirm that patients do not receive an optimal predialysis evaluation before being referred to the referral center. Conclusions: The Management of referrals for predialysis patients to the referral center is not adequate, and the proposal of a timely referral system to these specialized centers is necessary.